2012
DOI: 10.1002/ijc.27601
|View full text |Cite
|
Sign up to set email alerts
|

Body size and risk of differentiated thyroid carcinomas: Findings from the EPIC study

Abstract: Results from case-control and prospective studies suggest a moderate positive association between obesity and height and differentiated thyroid carcinoma (TC). Little is known on the relationship between other measures of adiposity and differentiated TC risk. Here, we present the results of a study on body size and risk of differentiated TC based on a large European prospective study (EPIC). During follow-up, 508 incident cases of differentiated TC were identified in women, and 58 in men. 78% of cases were pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
107
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 44 publications
11
107
3
3
Order By: Relevance
“…The association for adulthood BMI gain was restricted to men (HR for men = 1. did not materially change (data not shown). As observed previously (14), the HRs for height and BMI in EPIC did not materially change after excluding self-reported values (data not shown). Adjusting for history of benign thyroid conditions from the subset of studies with this information yielded similar results (data not shown).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The association for adulthood BMI gain was restricted to men (HR for men = 1. did not materially change (data not shown). As observed previously (14), the HRs for height and BMI in EPIC did not materially change after excluding self-reported values (data not shown). Adjusting for history of benign thyroid conditions from the subset of studies with this information yielded similar results (data not shown).…”
Section: Resultssupporting
confidence: 84%
“…Greater body mass index (BMI), a measure of total adiposity, has been associated with an increased risk of thyroid cancer in several observational studies (6,(8)(9)(10)(11)(12)(13)(14), with some exceptions (15)(16)(17)(18). Most of these studies also showed positive associations with greater height.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have consistently reported that individuals who are either overweight or obese are at an increased risk of thyroid cancer (23)(24)(25)(26)(27). The increasing trend of obesity might be another factor that accounts for some of the observed increasing incidence of thyroid cancer, although the degree of its contribution is unclear.…”
Section: Thyroid Cancer Epidemic 477mentioning
confidence: 99%
“…4 Today, more patients receive a TC diagnosis after an evaluation of an incidentally found thyroid nodule than after evaluation of a symptomatic or palpable nodule. 4 A contribution of known TC risk factors (environmental or medical radiation, 5 deficit or excess of iodine intake, 2 body mass, including being overweight or tall 6 ) or suspected risk factors (dietary aspects, 7 nitrates and nitrites, certain microelements in the diet or drinking water, 8 etc.) to TC incidence increases has been neither proven nor ruled out.…”
mentioning
confidence: 99%